2022
DOI: 10.1111/csp2.12668
|View full text |Cite
|
Sign up to set email alerts
|

The specter of empty countrysides and wetlands—Impact of hunting take on birds in Indo‐Burma

Abstract: Hunting for the wild meat trade, medicines and other human uses has decimated Indo‐Burma's vertebrate biota and has led to widespread defaunation. Yet, there is surprisingly little data on how hunting impacts wild bird assemblages in different landscapes here. Based on concurrent snapshot surveys of bird hunting, food markets and hunting attitudes across six Indo‐Burma countries, we found that hunting threatens species not only in forested landscapes but also wetlands and farmlands such as orchards and paddy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Thus, the ecological impact of bird hunting is not limited to just affecting the structure of the bird community through reduction in species richness and abundance (Benitez‐Lopez et al, 2017) but also implies the loss of ecosystem services that are crucial for human societies (Ramachandran et al, 2017). While hunting occurs in all bird habitats, the avifauna of wetlands are more vulnerable than others due to the predominant impact of anthropogenic exploitation, interacting with increased human accessibility and habitat degradation (Brotherton et al, 2020; Wetland International, 2010; Yong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the ecological impact of bird hunting is not limited to just affecting the structure of the bird community through reduction in species richness and abundance (Benitez‐Lopez et al, 2017) but also implies the loss of ecosystem services that are crucial for human societies (Ramachandran et al, 2017). While hunting occurs in all bird habitats, the avifauna of wetlands are more vulnerable than others due to the predominant impact of anthropogenic exploitation, interacting with increased human accessibility and habitat degradation (Brotherton et al, 2020; Wetland International, 2010; Yong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of hunting on wetland bird populations have been extensively recorded in many parts of Asia, and the bird harvest has already surpassed its sustainable thresholds (Gallo‐Cajiao et al, 2020). In seven countries of the Indo‐Burma region, a recent study by Yong et al (2022) revealed that 47 wetland bird species were trapped or netted in wetlands and associated cultivated lands. Large‐scale netting and trapping of birds is of particular concern in wetlands that overlap with global flyways (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such netting is illegal in some areas, for example, Victoria, Australia (State Government of Victoria, 2019). In many Asian countries however, including Thailand, legal interpretation regarding restrictions on netting in agricultural landscapes is ambiguous, and regulations are poorly enforced; hence netting is still widely used (e.g., Yong et al, 2022). In addition to illegal intentional captures for local consumption (e.g., Chowdhury, 2010;Kasper et al, 2020;Xayyasith et al, 2020;Zöckler et al, 2010), recreation (e.g., Chang et al, 2019), merit-making release (e.g., Gilbert et al, 2012), pets (e.g., Harris et al, 2017;Nijman et al, 2018;Wang, Shi, et al, 2021), or trafficking (e.g., Heim et al, 2021;Heinrich et al, 2020), collateral damage through the use of nets and other preventive means is likely to be a significant threat to certain species.…”
Section: Introductionmentioning
confidence: 99%
“…Netting has long been indiscriminately used in pest management across different types of production landscapes in many regions including ricefields, other field crops, orchards, and aquaculture ponds (e.g., Anderson et al, 2013; Bomford & Sinclair, 2016; Russell et al, 2012; Wang et al, 2020; Yong et al, 2022), particularly in Indo‐Burma, one of the world's most important biodiversity hotspots (Hu et al, 2020; Myers et al, 2000). Netting is widely believed to be the most effective, albeit costly, method of bird control (Anderson et al, 2013; Firake et al, 2016; Lindell, 2020).…”
Section: Introductionmentioning
confidence: 99%